(untitled) (Journal of actual problems of jurisprudence, 2023)
The development of quality laws is the key to the country’s next sovereign and prosperous day without corruption. This fact makes this study relevant. Reducing corruption risks in the development of regulations is crucial to ensure transparent and accountable governance. Analysis of international experience on reduction of corruption risks in the process of drafting of legislative acts in the countries with the lowest level of corruption will allow to draw general patterns to reduce corruption risks in the development of regulatory instruments (hereinafter - RI), which in turn will contribute to the development of practices of transparent and accountable governance. The purpose of the study is to review and analyze international experience in reducing corruption risks in the development of regulations in countries with low levels of corruption. The goal is achieved by solving the following tasks: a review of international corruption rankings to identify the countries with the lowest level of corruption, derived general rules to reduce corruption risks in the development of RI in countries with low levels of corruption. The scientific and practical significance of the study lies in the development through the synthesis of recommendations to reduce corruption risks in the drafting of RI. Key words: International experience in combating corruption, development of normative legal acts, anticorruption expertise.